When parks work: Effect of anthropogenic disturbance on occupancy of tropical forest mammals. Issue 9 (16th April 2020) - Oberosler, Valentina; Tenan, Simone; Zipkin, Elise F.; Rovero, Francesco
Abstract: Protected areas (PAs) in the tropics are vulnerable to human encroachment, and, despite formal protection, they do not fully mitigate anthropogenic threats to habitats and biodiversity. However, attempts to quantify the effectiveness of PAs and to understand the status and changes of wildlife populations in relation to protection efficiency remain limited. Here, we used camera‐trapping data collected over 8 consecutive years (2009–2016) to investigate the yearly occurrences of medium‐to‐large mammals within the Udzungwa Mountains National Park (Tanzania), an area of outstanding importance for biological endemism and conservation. Specifically, we evaluated the effects of habitat and proxies of human disturbance, namely illegal hunting with snares and firewood collection (a practice that was banned in 2011 in the park), on species' occurrence probabilities. Our results showed variability in species' responses to disturbance: The only species that showed a negative effect of the number of snares found on occurrence probability was the Harvey's duiker, a relatively widespread forest antelope. Similarly, we found a moderate positive effect of the firewood collection ban on only the suni, another common antelope, and a negative effect on a large opportunistic rodent, the giant‐pouched rat. Importantly, we found evidence of temporal stability in occurrence probability for all species over the 8‐year study period. Our findings suggest that well‐managed PAs can sustain mammal populations in tropical forests. However, variability among species in their responses to anthropogenic disturbance necessitates consideration in the design of conservation action plans for multiple taxa. Abstract : Protected areas (PAs) in the tropics are vulnerable to human encroachment, but attempts to quantify their effectiveness remain limited. We used camera‐trapping data collected over 8 consecutive years to evaluate the effects of proxies of human disturbance on the yearly occurrences of forest mammals within the Udzungwa Mountains National Park (Tanzania). Our results showed variability in species' responses to disturbance, and we also found evidence of temporal stability in occurrence probability for all species over the study period, suggesting that well‐managed PAs can sustain mammal populations in tropical forests.